Entre Anas: textualidade feminina em Ana Cristina Cesar e Ana Carolina Soares - Anselmo, Mariana (2021)
This study assays the (im)possibility of a woman's textuality in female literature and cinema, bringing together the poetic text of the writer Ana Cristina Cesar in selected poems from the book A teus pés (1982) and the filmic text Sonho de Valsa (1987) by the filmmaker Ana Carolina. Considering that literature and cinema maintain a series of possible relationships with each other, as discussed by Bazin (1961), the hypothesis that these works are influenced by two perspectives is investigated: through the intertextuality perspective (PERRONE- MOISÉS, 1978), as far as the works are presented as a fragmentary plot, woven from devotion procedures, appropriation and collage of voices, texts and plural artistic procedures; and through the female enjoyment (BRANCO, 1989; BRANDÃO, 1989) insofar as eroticism is the driving force of formal, aesthetic and social transgressions that mark these textures (LORDE, 1984). In the first part, the authors are situated in their historical and contextual dimension and in their respective scenarios of action, based on studies by Malufe (2008), Mocarzel (2008), Moriconi (2016), Soares (2012), Süssekind (1998), the aim is thus to understand its position under the female condition. Subsequently, the transgressions operated in the texts, which move by the force of enjoyment and eroticism in the feminine territory are discussed. Finally, the collapse of romanticized love is articulated with the grasping of ecstasy by the woman in the textual surface of the works, seeking to demonstrate the in-between places in which Anas find themselves.